1992
DOI: 10.1017/s0047404500015013
|View full text |Cite
|
Sign up to set email alerts
|

Social network and social class: Toward an integrated sociolinguistic model

Abstract: In sociolinguistics, approaches that use the variables of socioeconomic class and social network have often been thought to be irreconcilable. In this article, we explore the connection between these variables and suggest the outlines of a model that can integrate them in a coherent way. This depends on linking a consensus-based microlevel of network with a conflict-based macrolevel of social class. We suggest interpretations of certain sociolinguistic findings, citing detailed evidence from research in Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
163
0
15

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(179 citation statements)
references
References 21 publications
1
163
0
15
Order By: Relevance
“…highest status social class, tend to represent loans from other high-prestige speech (Labov, 1994: 78). Milroy and Milroy (1992) have also attempted to study linguistic change by understanding the role of social class and network. According to their findings (1992:4), "the level of integration of any given group into the wider society is likely to be inversely related to the extent to which it maintains a distinctive vernacular", and all the shifts occurring "will be constrained by variations in political, economic, and social structures that are specific to these different localities".…”
Section: Decoding a Sociolect Through Text-samplesmentioning
confidence: 99%
“…highest status social class, tend to represent loans from other high-prestige speech (Labov, 1994: 78). Milroy and Milroy (1992) have also attempted to study linguistic change by understanding the role of social class and network. According to their findings (1992:4), "the level of integration of any given group into the wider society is likely to be inversely related to the extent to which it maintains a distinctive vernacular", and all the shifts occurring "will be constrained by variations in political, economic, and social structures that are specific to these different localities".…”
Section: Decoding a Sociolect Through Text-samplesmentioning
confidence: 99%
“…Work in the sociolinguistic field has also combined network analysis and linguistic style to understand linguistic variation with respect to social position (29), although with the social position provided from external sources. Eckert (11) describes the tradition in sociolinguistics of studying style variation in relation to "social categories of socioeconomic class, sex class, and age," at work in "ethnographic studies of more locally-defined populations" and "as a resource for the construction of social meaning."…”
Section: Related Sociolinguistic Workmentioning
confidence: 99%
“…Indeed, it has often been observed that social networks are the locus of ethnic and/or ideological affiliations (Bortoni-Ricardo 1985;Edwards 1986;Milroy 1987;Milroy and Milroy 1992). The relationship between network membership and ideology is one that warrants further investigation in this community.…”
Section: ~-----------------------------------mentioning
confidence: 99%